Experimental dry socket: microscopic and molecular evaluation of two treatment modalities Alveolite experimental: análise microscópica e molecular de duas modalidades de tratamento - Camila Lopes Cardoso; Osny Ferreira Júnior; Paulo S. Perri de Carvalho; Thiago José Dionísio; Tânia Mary Cestari; Gustavo Pompermaier Garlet (Acta Cirúrgica Brasileira, 2011)
PURPOSE: To evaluate two treatment modalities of dry socket in rats and to discuss the first findings of the molecular analysis in this experimental model. METHODS: 84 rats underwent a tooth extraction were divided in 4 groups: I-uninfected socket (control), II-infected socket without any treatment, III-infected socket treated with irrigation of 2% sodium iodide and 3% hydrogen peroxide solution, IV-infected socket submitted to curettage, irrigation with physiological saline solution and fulfilled with metronidazole paste as base. The groups were subdivided in postoperative sacrifice periods: 6/15/28 days. A quantitative and a qualitative microscopic analysis was performed. Also, a quantitative analysis was performed using a RealTimePCR to evaluate the genes expression in the wound healing: Collagen Type I/COL-I, vascular endothelial growth factor/VEGF, osteocalcin/OCN, alkaline phosphatase/ALP, runt-related transcription factor 2/RUNX2 and tumor necrosis factor alpha/TNF-α. RESULTS: The group I showed higher bone formation, followed by groups IV, III, II respectively. The group II presented higher inflammatory infiltrate and the wound healing was delayed compared with other groups. It was obtained a significant positive correlation between bone neoformation and the expression of OCN and RUNX2, inflammatory infiltrate with TNF-α and a negative correlation between bone neoformation and TNF-α. CONCLUSION: No significant difference was found between the treatments. OBJETIVO: Avaliar duas modalidades de tratamento da alveolite em ratos e discutir os primeiros achados de uma análise molecular neste modelo experimental. MÉTODOS: 84 ratos foram submetidos a uma extração dentária e foram divididos em quatro grupos: I- alvéolo não infectado (controle), II- alvéolo infectado sem tratamento, III- alvéolo infectado tratado com irrigação de iodeto de sódio a 2% e solução de peróxido de hidrogênio a 3%, IV- alvéolo infectado submetido à curetagem, irrigação com solução salina fisiológica e preenchimento com pasta a base de metronidazol. Os grupos foram subdivididos em períodos de sacrifício pós-operatório: 6/15/28 dias. Uma análise quantitativa e qualitativa microscópica foi realizada. Além disso, uma análise quantitativa foi realizada utilizando RealTimePCR para avaliar a expressão de genes no reparo alveolar: o colágeno tipo I / COL-I, o fator de crescimento endotelial vascular / VEGF, osteocalcina / OCN, fosfatase alcalina / ALP, fator de transcrição runt relacionados 2 / RUNX2 e fator de necrose tumoral alfa / TNF-α. RESULTADOS: O grupo I mostrou maior formação óssea, seguido pelos grupos IV, III, II, respectivamente. O grupo II apresentou maior infiltrado inflamatório e a cicatrização foi atrasada em comparação com outros grupos. Foi obtida uma correlação positiva entre a neoformação óssea e a expressão de OCN e RUNX2, infiltrado inflamatório com TNF-α e uma correlação negativa entre a neoformação óssea e TNF-α. CONCLUSÃO: Nenhuma diferença significativa foi encontrada entre os tratamentos.